Analisis Faktor-Faktor Yang Mempengaruhi Ketimpangan Pendapatan di Provinsi Yogyakarta - Ningsih, Rizka Wahyu; Salma, Salma; Rabbani, Naufal; Maulana, Rajendra Kimi; Desmawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The focus of this research, which utilizes panel data, is to understand the dynamics of income inequality in the DI Yogyakarta region from 2014 to 2023. This study aims to identify the variables that influence income inequality. The results of the study indicate that the average length of schooling has an impact on income inequality. On the other hand, factors such as the Human Development Index, Provincial Minimum Wage, and Open Unemployment Rate are proven to have no significant effect on the issue of income inequality in the research area. Income inequality is a critical issue that hinders development in many countries, including Indonesia.